Development of a method based on HPLC-DAD for the detection and quantification of glutamate and gamma-aminobutyric acid - Machado, Patrícia Alexandra Peixoto (2018)
Introduction: With the increasing incidence of neurodegenerative diseases, the need arose to study several molecules that may be useful to the study of new therapies and to treat the symptoms that come with these diseases, as is the case of depression. GABA and glutamate have a very important role in the homeostasis of the organism and molecules of interest and potential from the point of view of diagnosis are revealed. HPLC is a method that allows the detection and quantification of various analytes in different biological matrices, allowing rapid results with high precision, sensitivity and specificity. Objectives: Perform a meta-analysis to understand the role of depression in neurodegenerative diseases and develop a simple, fast, non-derivatizing method based on HPLC-DAD for the detection and quantification of GABA and glutamate. To test its applicability in several biological matrices, so that it can be used as an additional tool for the study of neurodegenerative pathologies. Materials and methods: The validation of the developed method was performed according to ICH guidelines, which was tested in standard solutions of GABA and glutamate and in samples of serum, urine and yeast extract. All assays were performed using a Hitachi LaChrom Elite HPLC system, with separation on a Lichrospher LiChroCART 250-4 100 (5 m) RP-18 column and with DAD detection. Results: At the end of several assays, the chosen method has as mobile phase H2O and acetonitrile, eluted in gradient, at a flow rate of 1 mL/min for 10 minutes. The column temperature was 25 and the detection was performed at 210 nm. This method not only allows a rapid analysis but also a quantification in the order of g/mL. Although the quantification was possible in the standard solutions, the same did not occur in the biological matrices tested. Conclusion: Although it still needs to be optimized for biological matrices, the method developed allows an easy, fast and economically sustainable analysis of GABA and glutamate. It is, to date, the only method with DAD detection that allows the simultaneous detection of GABA and glutamate without recourse to derivatization of the sample.